The relationship between diaphragm thickness and the severity of the disease in pregnant patients with Covid-19 - Eda Ureyen Ozdemir; Gul Nihal Buyuk; Dilek Acar; Burak Elmas; Gamze Yilmaz; Namik Nebi Özcan; Hüseyin Levent Keskin; Özlem Moraloglu Tekin (Elsevier, 2023)
Objective: We aimed to investigate whether there is a relationship between diaphragm thickness and disease severity in Covid-19 pregnant subgroups. Material and methods: In this prospective study 100 pregnant patients were enrolled. Thickness of the diaphragm muscle at end-expiration was measured using B-Mode US. Hemoglobin,WBC, NLR, procalcitonin and LDH levels were measured. Results: There was a statistically significant difference between the groups in terms of diaphragm thickness, and the diaphragm thickness was thinner in the severe disease group (p < 0.001). There was no statistically significant difference between the groups with mild to moderate disease severity (p = 0.708). Conclusion: Covid-19 patients who developed serious infection has thinner diaphragms than those who did not. Low diaphragm muscle thickness at the outset of Covid-19 disease, may predispose to poor clinical outcomes. Diaphragmatic ultrasound may be a promising tool to evaluate the risk of Covid-19 disease severity.